Bases for a New Maritime Delimitation for Panama in The Caribbean Sea and The Pacific Ocean - Chávez Rodríguez, Yovani Edgar (Ius Humani. Jornal do direito, 2025)
The Exclusive Economic Zone (EEZ) represents a delimited maritime space in which States exercise sovereignty based on certain rights and duties established in the 1982 United Nations Convention on the Law of the Sea (UNCLOS). However, Panama's EEZ remains in an irregular situation, as it does not cover 200 nautical miles and lacks direct access to the high seas, despite the fact that the Panama Canal constitutes an international access route for all nations. From this perspective, this article analyzes the need to guarantee Panama direct access to the high seas, as well as the problematic interpretations of countries regarding their EEZs and the underlying role of the past military occupation of Panama by the United States of America. Similarly, it analyzes the role of colonialist reminiscences and the connotations of the current legal framework. Finally, it presents a proposal for a new EEZ in the Caribbean Sea and the Pacific Ocean, as well as the respective course of action before the International Court of Justice to achieve this objective in the event that negotiations fail. Therefore, Panama must base its claims on the principle of equal rights among nations, the right of access to the high seas, and the security of the Panama Canal. Although the decisions issued by the International Court of Justice may have repercussions for Colombia, Costa Rica, and Nicaragua, Panama deserves to be taken into account in the concert of nations.